The Effectiveness of the Process of Developing the Life Quality of the Elderly under the Sufficiency Economy: A Case Study Lom Kao District, Phetchabun Province - ผลประเสริฐ, พิมพ์รพี; วิทยถาวรวงศ์, พรรณพิศ (Journal of Preventive Medicine Association of Thailand, 2018)
Most of elderly have encountered with problems that affect their well-being and quality of life. An important care for elderly is enabling seniors to have good quality of life. The idea of applying the learning process in improving the quality of life for the elderly under the sufficiency economy. The purpose of this experimental research was to study the effectiveness of the learning process in improving the quality of life for the elderly in Lom Kao district, Phetchabun Province. Sixty of elderly in Lom Kao district, Phetchabun province were purposively selected to an experimental group (30 samples) and a control group (30 samples). Selected a specific sample (Purposive Sampling) of Elderly 60 years old and over, Can speak well, Perfectly sensible and willing to participate in the study. The experimental group was joined by the group learning program.; The control group was given the program taught the usual manner. Data were collected before and after program implementation using aquestionnaire with 3 sections: general information, the application of the principles of the sufficiency economy philosophy (reliability=.77) and Quality of life of the elderly (reliability=.84). Statistics applied for data analysis included frequency, percent, mean, standard deviation, paired t-test, and independent t-test. The results found that: 1) For an experimental group, after program implementation, mean scores of the sufficiency economy philosophy, and Quality of life of the elderly were significantly higher than those before program implementation. 2) After participating in the participatory learning program, the sufficiency economy philosophy of an experimental group were higher than those a control group statistically significant at the 0.05 level. No statistically significant difference for the social and cultural issues. Quality of life of the elderly of an experimental group were higher than those a control group statistically significant at the 0.05 level, except in issues of being in a good temper and interpersonal relationships, no statistically different found. This study suggests that health authorities and other relevant agencies should apply group learning process to guide the application of the principles of the sufficiency economy philosophy that is the guidelines for developing the life quality of the elderly under the sufficiency economy in Phetchabun province and other provinces tobe a quality senior.